Identification of Bioactive Compounds from Cocoa Fruit Skin ( Theobroma Cacao L.) with Variations in Solvent Polarity Properties - Ahlan Sangkal; Julia Megawati Djamal; Rifani Hutami Supardi (International Journal Of Health Science, 2025)
Bioactive compounds are chemical compounds formed through metabolic processes in plants, contributing to their beneficial properties. Cocoa fruit, derived from 22 cultivated Theobroma species, contains a variety of bioactive compounds that offer several health benefits. Identifying these bioactive compounds in plants can be achieved through extraction using various solvents, depending on their polarity properties. This study aims to explore the content of bioactive compounds in dried cocoa fruit peel (Theobroma cacao L.) extract, focusing on variations in solvent polarity. The results of the study showed that the 96% ethanol extract (polar solvent) of cocoa fruit peel contained a range of bioactive compounds, including flavonoids, tannins, alkaloids, and saponins. Ethanol, being a polar solvent, effectively extracted a variety of bioactive compounds due to its ability to dissolve polar substances. This extract is significant due to its wide range of potential health benefits attributed to the presence of flavonoids, tannins, alkaloids, and saponins, all known for their antioxidant, antimicrobial, and anti-inflammatory properties. Additionally, the acetone extract (semi-polar solvent) of cocoa fruit peel also contained alkaloids, flavonoids, tannins, and saponins. Acetone, as a semi-polar solvent, was able to extract a variety of compounds with moderate polarity, making it a versatile solvent for bioactive compound extraction. The presence of alkaloids and saponins in this extract indicates its potential use for various medicinal purposes. On the other hand, the n-Hexane extract (non-polar solvent) of cocoa fruit peel produced primarily alkaloids and terpenoids. Hexane, being non-polar, tends to extract non-polar compounds, which include alkaloids and terpenoids known for their various biological activities. In conclusion, the study demonstrates the varying effectiveness of solvents with different polarities in extracting bioactive compounds from cocoa fruit peel, which can be utilized for health-promoting purposes.